Low-cost environmental chamber for battery calendar aging under tropical conditions: design and validation - Uvi Desi Fatmawati; Iwa Garniwa; Faiz Husnayain; Danang Lelono; Kuwat Triyana; Amelia Chandra Pratiwi (Universitas Ahmad Dahlan, 2026)
This study presents a low-cost environmental chamber designed to replicate tropical temperature and humidity conditions for calendar-aging studies of LiFePO₄ lithium iron phosphate (LFP) cells. The system integrates passive insulation with an Arduino-based active control system for real-time monitoring. The design’s novelty lies in its cost-effective ability to maintain tropical-specific profiles, validated against Meteorology, Climatology, and Geophysics Agency (BMKG) meteorological data to ensure correlation with diurnal cycles. Experimental results demonstrate stable operation for 13 consecutive days, with an average temperature of 29.47 °C and a stability metric of ±0.61 °C, keeping 100% of data within the 25–35 °C target. Although relative humidity (RH) showed an average of 76.52%, its stability was quantified by a 96.98% success rate in maintaining the 70–80% target range. The chamber’s suitability for long-term degradation studies was confirmed via a one-month calendar-aging test on a 15 Ah LFP cell, where tha battery capacity decreased from 100% to 99.58%. These results demonstrate that the proposed chamber reliably maintains tropical environmental conditions and is suitable for long-term, low-cost battery aging studies.